Sebelum Peristiwa Pemberontakan 1926: Perebutan Ruang Publik Sarekat Rakyat di Priangan, 1920-1926 - Dharyanto Tito Wardani; A. Fadhilah Utami Ilmi Rifai (Perkumpulan Program Studi Sejarah Se-Indonesia, 2026)
In the periodization of the national movement in Indonesian history, indigenous intellectual resistance was carried out through modern organizations, one of which was the Sarekat Islam, which split, with the left faction forming the Sarekat Rakyat. This study aims to reconstruct and analyze the struggle for public space and the dynamics of ideological conflict within the Sarekat Islam organization, culminating in the formation of the Sarekat Rakyat in the Priangan region before the 1926 rebellion. The research method used is the historical method consisting of four stages of work: heuristics, criticism, interpretation, and historiography (explanation). The concepts and theories used are the concepts and theories of hegemony or power of Antonio Gramsci. The results of this study conclude that the history of the national movement through the modern Sarekat Islam organization experienced quite difficult developments. This difference began with the interests of each leader of the Sarekat Islam organization in their region, and there was always competition over the policies and strategic and political steps of the organization. The struggle for public space carried out by the Sarekat Rakyat in Priangan during 1920–1926 brought important changes to the political dynamics of society. Through public meetings (vergadering), propaganda, and various organizational activities, Sarekat Rakyat succeeded in transforming the public sphere into a vehicle for disseminating anti-colonial ideas and building popular political awareness. As a result, the public sphere, previously largely controlled by the colonial government and the Sarekat Islam group, became an arena for political contestation between Sarekat Rakyat, Sarekat Islam, the Indonesian Communist Party (PKI), and the Dutch East Indies government. This development strengthened Sarekat Rakyat's influence in Priangan but also triggered repressive measures by the colonial government, including surveillance, the disbandment of meetings, arrests of activists, and restrictions on political activity in the lead-up to the 1926 rebellion.